2016
DOI: 10.11113/jt.v78.8838
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Wireless Mobile Rfid Reader in Real World Industry Environment

Abstract: WIBRED is a new embedded system of Wireless Mobile Radio Frequency Identification (RFID) Reader is provide an approach of solving the complex tracking system of material flow in manufacturing industry. This new architecture is embedded with active RFID and passive RFID through wireless mesh network (WMN) platform and smart data processing adopted through web based tracking. RFID smart label solutions for cost effective to monitor and control the material flow in real time manner. The proposed architecture will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Consequently, any change in the production plan was communicated to the warehouse through IoT. Some other authors such as Zhuang et al [147], Semunab et al [139], Qu et al [134] and Qu et al [131] also suggested using RFID as a representative of IoT for planning and scheduling related activities. Zhang et al [133] developed an active sensing system of real-time and multisource manufacturing information.…”
Section: Category 2: Planning and Scheduling-related Activitiesmentioning
confidence: 99%
“…Consequently, any change in the production plan was communicated to the warehouse through IoT. Some other authors such as Zhuang et al [147], Semunab et al [139], Qu et al [134] and Qu et al [131] also suggested using RFID as a representative of IoT for planning and scheduling related activities. Zhang et al [133] developed an active sensing system of real-time and multisource manufacturing information.…”
Section: Category 2: Planning and Scheduling-related Activitiesmentioning
confidence: 99%